Knee Kinematics Following Anatomic Single vs. Double Bundle ACL Reconstruction: A Randomized Clinical Trial. Issue 7 (21st July 2017) - Tashman, Scott; Irrgang, James J.; Moore, Charity; Musahl, Volker; West, Robin Vereeke; Fu, Freddie H.
Objectives: A randomized clinical trial was conducted to compare knee kinematics during gait and running 24 months after ACL reconstruction, using either single-bundle (SB) or double-bundle (DB) quadriceps tendon grafts. We hypothesized that DB reconstruction would better restore kinematics than SB reconstruction, in comparison to the uninjured, contralateral knee. Methods: Subjects were between 14 and 50 years of age, participated in at least 100 hours of Level 1 or 2 sports activities and presented within 12 months of injury to both bundles of the ACL (with or without meniscal injury). Exclusion criteria included prior injury or surgery of the ipsilateral or contralateral knee or greater than a grade 1 concomitant knee ligament injury. Subjects were randomized to undergo SB or DB ACL reconstruction with a 10 mm quadriceps tendon autograft harvested with a patellar bone block. A single, anatomically placed femoral tunnel was used for all cases. For DB ACL reconstruction, the soft tissue portion of the graft was split and passed through two anatomically placed tibial tunnels. Biplane radiographic images were acquired 24 months after surgery while subjects performed downhill running on a treadmill (3.0 m/s, 10 degree slope, 150 images/s) and level gait (1.3 m/s, 100 images/s). Subject specific bone models were generated from computed tomography images and matched to the biplane radiographs using a previously validated model-based tracking process to determine tibiofemoral kinematics. Rotations of the tibia relative to the femur were calculated using the rotational component of the Joint Coordinate System originally described by Grood and Suntay. Displacements of the tibia relative to the femur were expressed in an orthogonal anatomical coordinate system fixed to the tibia. Primary outcome variables were based on previous findings of abnormalities in knee kinematics after ACL injury/reconstruction, and included peak knee external rotation, adduction and anterior translation during heelstrike to mid-stance. Three trials were collected for each limb and each task, and averaged for statistical analysis. Differences between SB and DB kinematics were determined using Wilcoxon Signed Rank tests, with significance level p < 0.05. Results: No significant differences were found in any of the primary kinematic variables between single and double bundle anatomic ACL reconstruction (Table). Differences between reconstructed and contralateral (uninjured) limbs were small, averaging less than 2 degrees in rotation and 2 mm in translation. Rotational differences were smaller during gait than during downhill running. Conclusion: Conclusions: Contrary to the study hypothesis, DB reconstruction was not found to be superior to SB reconstruction. While some abnormalities remained (particularly during the more stressful downhill running evaluation), both anatomical reconstructions were equally effective at restoring normal knee kinematics. kinematic differences between limbs (affected-contralateral) during gait and downhill running Single Bundle Single Bundle Single Bundle Double Bundle Double Bundle Double Bundle N Mean Std Dev N Mean Std Dev Wilcoxon p Running Peak Knee Adduction 25 -0.23 1.12 21 -0.21 1.16 0.71 Running Peak External Rotation 25 -1.56 4.04 21 -0.17 3.12 0.20 Running Peak Anterior Translation 25 0.57 2.62 21 2.02 2.75 0.13 Gait Peak Knee Adduction 26 -0.06 1.19 21 -0.05 1.11 0.83 Gait Peak External Rotation 26 -0.44 4.34 21 -0.11 3.55 0.77 Gait Peak Anterior Translation 26 0.83 2.97 21 2.00 2.56 0.20